KAJIAN PASAR MALAM DALAM RANGKA UPAYA MEMASARKAN PRODUK DAERAH DI KABUPATEN KUTAI KARTANEGARA - Midiansyah Effendi (Universitas 17 Agustus 1945 Samarinda, 2013)
The purpose of the study were: (1) identify the kinds and types of products that are marketed at a evening market activities, (2) identify the kinds and types of local products that are marketed, (3) identify the average amount of sales turnover of goods and services, (4) identify driving factors and obstacles encountered, and (5) develop and formulate evening market activities that can improve the economy of communities in Kutai Kertanegara Regency. Research carried out at the evening market spread over seven sub districts in the Kutai Kertanegara Regency, covered : Samboja, Muara Jawa, Sanga-Sanga, Anggana, Muara Badak, Marang Kayu and Kota Bangun for three months. Research activities include: observation, literature review, preparation and coordination, data collection, compilation and analysis of data, and reports writing. The data collected is: (1) secondary data obtained from various departments/agencies in the form of literature, study reports and annual reportsthat are relevant to the study, and (2) primary data obtained through direct observation and interviews with informants sources, both individually and collectively of the parties involved in the activity of the existing evening market in Kutai Kertanegara. Compilation of data is done in accordance with the needs analysis and the data were analyzed descriptively. The results showed that: 1. There are 9 kinds of products that are marketed at a evening market, they are: (a) rice, sugar, noodles, food seasoning and salt; (b) vegetables and fruits; (c) red onion, garlic and spices; (d) fabrics, clothes, socks, and slippers; (e) fish, eggs and meat; (f) miscellaneous/accessories goods; (g) electrical appliance, electronic and cassette/CD; (h) fishing equipment and (i) services. 2. There are 4 local products that are marketed at a evening market, they are: (a) food, snack, and beverages; (b) vegetables, (c) fruit, and (d) fish, eggs and meat. 3. The average amount of sales turnover of goods and services are marketed in the evening market is Rp. 300,000,- to Rp. 1.000.000,- per seller per activity. 4. Driving factors that determine the activities in the evening market cover: (a) the price of goods and services sold is cheap, (b) the goods are sold variegated; (c) a mean of entertainment in the evenings for surrounding communities; (d) spare time factor for employee/employees who work and do not have time during the day shopping, and (e) the affordability factor, so effective and efficient in terms of time and transport. 5. Inhibiting factors/constraints faced in the evening market activity include: (a) the absence of a permanent location so that tends to disturb the public order, (b) not be developed by the relevant agencies, (c) the unavailability of adequate facilities concerning parking lot, garbage, toilets, electricity, and clean water; (d) the safety and hygiene is not optimal, and (e) the absence of Perda and Perbup about the evening market. 6. In future, it is expected to form formulation of activities of the evening market which is able to improve the community's economy, through: (a) made the rules such as laws (Perda, Perbup), so that legality of evening market exist, (b) conducted surveillance on all products that are marketed/sold in the evening market; (c) facilities and infrastructure necessary to build, such as parking lot, electricity, clean water, and garbage place, for the convenience of the evening market, (d) the need for determining the exact location of the evening market: and (e) shall be increased hygiene and safety; (f) there is easy access to the get more capital through banks and cooperatives; (g) clarity on parties collect fees in accordance with laws; (h) coaching and training to the parties involved in evening market activities, to be managed by qualified, professional, prosperous and fair, and (i) a solution to overcome unemployment.